Professionals' perspectives on the challenges of implementing digital solutions in rehabilitation settings in Rwanda - Jokinen, Kaisa; Oduor, Michael; Urimubenshi, Gerard; Gasana, Juliette; Bigirimana, Jean Damascene; Tumusiime, David K.; Aartolahti, Eeva; Murtonen, Kari-Pekka; Korniloff, Katariina (Frontiers in Digital Health, 2025)
The need for rehabilitation is unmet, especially in low- and middle-income countries such as Rwanda. Digital rehabilitation offers significant potential for delivering rehabilitation services in low-resource settings, and this study examines the challenges affecting the digitalization of rehabilitation. Semi-structured interviews and a survey were conducted in Rwanda with rehabilitation professionals to collect data for two different projects. The different datasets were analyzed using thematic analysis and inductive content analysis. As a result, three main concepts were formed: context-related factors, individual-related factors, and technology-related factors. Results suggest that the challenges in implementing digital solutions in rehabilitation settings in Rwanda encompass various domains, including socioeconomic factors, infrastructure, digital competency, regulatory frameworks, and user-related factors. In conclusion, because of multifaceted challenges, systemic-level change is needed to realize the potential of the digitalization of rehabilitation and other health care services in Rwanda.